2020
DOI: 10.1016/j.cell.2019.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Toxicity Drives Age-Related Mitochondrial Decline by Altering Iron Homeostasis

Abstract: Mitochondria and lysosomes are functionally linked, and their interdependent decline is a hallmark of aging and disease. Despite the long-standing connection between these organelles, the function(s) of lysosomes required to sustain mitochondrial health remains unclear. Here, working in yeast, we show that the lysosome-like vacuole maintains mitochondrial respiration by spatially compartmentalizing amino acids. Defects in vacuole function result in a breakdown in intracellular amino acid homeostasis, which dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
152
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 115 publications
(155 reference statements)
7
152
0
2
Order By: Relevance
“…For example, because of the dependence of transferrin-mediated iron uptake upon an acidic lysosomal pH, lysosomal defects cause a deficiency of intracellular iron. Iron depletion is a major toxic consequence of lysosomal dysfunction in yeast and mammalian cells (Hughes et al, 2020;Weber et al, 2020). Previous work largely attributed the deleterious effects of iron deficiency to mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, because of the dependence of transferrin-mediated iron uptake upon an acidic lysosomal pH, lysosomal defects cause a deficiency of intracellular iron. Iron depletion is a major toxic consequence of lysosomal dysfunction in yeast and mammalian cells (Hughes et al, 2020;Weber et al, 2020). Previous work largely attributed the deleterious effects of iron deficiency to mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…We next employed the WT hs strain to investigate the importance of vacuolar and mitochondrial functions in regulating the labile heme pool in the cytosol. Several studies have demonstrated roles for the vacuole and mitochondria in the regulation of iron homeostasis (45)(46)(47)(48)(49)(50)(51)(52)(53). However, little is known about the roles of these organelles in the regulation of heme uptake and intracellular heme homeostasis in fungal pathogens.…”
Section: Characterization Of a Cytosolic Heme Sensor For C Neoformansmentioning
confidence: 99%
“…Treatment with the ATP synthase 182 inhibitor oligomycin, mitochondrial depolarizing agents antimycin A and FCCP, hypoxia 183 mimetic CoCl2, the ER stress inducer tunicamycin, or the oxidant hydrogen peroxide did 184 not induce MDC formation ( Figure S2A). Likewise, MDCs were not induced when cells 185 were treated with the iron chelator BPS ( Figure S2B), and iron addition to concA-treated 186 cells, which is sufficient to restore mitochondrial respiration in the absence of a 187 functioning vacuole (Chen et al, 2020;Hughes et al, 2020), did not inhibit concA-188 induced MDC formation ( Figure S2B). Together, these results suggest that MDCs are 189 not responsive to typical mitochondrial stressors, including loss of mitochondrial 190 membrane potential, oxidative stress, ATP depletion, or iron deprivation.…”
mentioning
confidence: 97%
“…We recently discovered that the yeast lysosome (vacuole) functions as a 88 safeguard against cellular amino acid toxicity through its ability to import and sequester 89 amino acids (Hughes and Gottschling, 2012;Hughes et al, 2020). Defects in vacuolar 90 amino acid compartmentation impair mitochondrial respiration and negatively impact 91 cellular health (Hughes and Gottschling, 2012;Hughes et al, 2020). In addition, prior 92 work in yeast has shown that the regulation of plasma membrane (PM)-localized 93 indicating that MDCs form in direct response to loss of lysosome acidification (Figures 140 S1A-D).…”
mentioning
confidence: 99%